A Plutocratic Proposal: an ethical way for rich patients to pay for a place on a clinical trial. Issue 11 (6th June 2017) - Masters, Alexander; Nutt, Dominic
Abstract : Many potential therapeutic agents are discarded before they are tested in humans. These are not quack medications. They are drugs and other interventions that have been developed by responsible scientists in respectable companies or universities and are often backed up by publications in peer-reviewed journals. These possible treatments might ease suffering and prolong the lives of innumerable patients, yet they have been put aside. In this paper, we outline a novel mechanism—the Plutocratic Proposal—to revive such neglected research and fund early phase clinical trials. The central idea of the Proposal is that any patient who rescues a potential therapeutic agent from neglect by funding early phase clinical trials (either entirely or in large part) should be offered a place on the trial.